Molecular Insights into the dynamics of pharmacogenetically important N-terminal variants of the human beta(2)-adrenergic receptor - Shahane, Ganesh; Parsania, Chirag; Sengupta, Durba; Joshi, Manali (Plos Computational Biology, 2014)
The human beta(2)-adrenergic receptor (beta(2)AR), a member of the G-protein coupled receptor (GPCR) family, is expressed in bronchial smooth muscle cells. Upon activation by agonists, beta(2)AR causes bronchodilation and relief in asthma patients. The N-terminal polymorphism of beta(2)AR at the 16th position, Arg16Gly, has warranted a lot of attention since it is linked to variations in response to albuterol (agonist) treatment. Although the beta(2)AR is one of the well-studied GPCRs, the N-terminus which harbors this mutation, is absent in all available experimental structures. The goal of this work was to study the molecular level differences between the N-terminal variants using structural modeling and atomistic molecular dynamics simulations. Our simulations reveal that the N-terminal region of the Arg variant shows greater dynamics than the Gly variant, leading to differential placement. Further, the position and dynamics of the N-terminal region, further, affects the ligand binding-site accessibility. Interestingly, long-range effects are also seen at the ligand binding site, which is marginally larger in the Gly as compared to the Arg variant resulting in the preferential docking of albuterol to the Gly variant. This study thus reveals key differences between the variants providing a molecular framework towards understanding the variable drug response in asthma patients.